(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The grammar–translation method (GTM) is one of the oldest and most enduring approaches in the Russian language teaching. Rooted in classical education, it prioritizes grammatical accuracy, translation skills, and reading comprehension through the systematic use of learners’ native language. Despite sustained criticism for its limited attention to communicative competence, the method continues to influence language pedagogy, particularly in academic, philological, and translation-oriented contexts. This thesis examines the theoretical foundations, instructional principles, strengths, and limitations of the grammar–translation method, while also reconsidering its potential role in modern the Russian language education. The analysis demonstrates that, when applied selectively and in combination with contemporary approaches, GTM can remain pedagogically meaningful.